How Does Isolated Medial Patellofemoral Ligament Reconstruction Influence Patellar Height?. Issue 4 (March 2020) - Luceri, Francesco; Roger, Julien; Randelli, Pietro Simone; Lustig, Sébastien; Servien, Elvire
Background: Reconstruction of the medial patellofemoral ligament (MPFL) is the gold standard treatment for recurrent patellar dislocation. Patella alta has been reported in about half of patients with recurrent patellofemoral instability. Hypothesis: MPFL reconstruction (MPFLr) has a beneficial role in the correction of patellar height in patients with mild patella alta (Caton-Deschamps index [CDI] between 1.20 and 1.40). Study Design: Case series; Level of evidence, 4. Methods: Skeletally mature patients, with no history of previous or concomitant knee surgical procedures, who underwent isolated MPFLr using hamstring autograft for recurrent patellar instability between 2005 and 2018, were included in this study. The authors calculated CDI, modified Insall-Salvati index (MISI), and Blackburne-Peel index (BPI) ratios. Measurements done by 2 independent observers were calculated and used to compare pre- and postoperative patellar height (patella alta: CDI >1.20). Results: A total of 89 patients (95 knees) were included in the study, with a mean age of 25.0 years (range, 15.0-45.0 years). There were 70% women and 30% men. We found patella alta in 35.8% of cases preoperatively. Among them, 79.4% had reduced patellar height indices, within normal limits, postoperatively (mean follow-up, 18.4 ± 12.0 months). All the ratios showed a significant reduction in patellar height after surgery (CDI: 0.19 [range, –0.05, 0.60]; MISI: 0.22 [–0.14, 0.76]; BPI: 0.18 [–0.08, 0.59]; P < .00001). The CDI of 79.4% of the study knees was reduced to within normal limits postoperatively. The CDI was maintained within normal limits postoperatively in 93.4% of the knees with normal patellar height and reduced to normal in 50% of the knees with severe patella alta before surgery . No patient reported patella infera before surgery, whereas this condition was found in 8.2% of study patients postoperatively. A moderate correlation was reported between preoperative radiographic indices and their reduction after surgery (CDI: P < .001, ρ = 0.39; MISI: P < .001, ρ = 0.39; BPI: P < .001, ρ = 0.48). Conclusion: The higher the preoperative patellar height, the more important is the lowering effect of MPFLr using the hamstring for patellar instability. Bony procedures should not be indicated in patients with patellar instability and a CDI between 1.20 and 1.40.